ChemInform Abstract: Heterogeneous Platinum‐Catalyzed C—H Perfluoroalkylation of Arenes and Heteroarenes. Issue 31 (August 2015) - He, Lin; Natte, Kishore; Rabeah, Jabor; Taeschler, Christoph; Neumann, Helfried; Brueckner, Angelika; Beller, Matthias
Abstract An operationally simple protocol for the direct perfluoroalkylation of a broad scope of aryl and heteroaryl compounds with perfluoroalkyl iodide or bromide is presented.